2018
DOI: 10.1038/s41598-018-28561-0
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin alleviates low-sulfur stress by promoting sulfur homeostasis in tomato plants

Abstract: Despite involvement of melatonin (MT) in plant growth and stress tolerance, its role in sulfur (S) acquisition and assimilation remains unclear. Here we report that low-S conditions cause serious growth inhibition by reducing chlorophyll content, photosynthesis and biomass accumulation. S deficiency evoked oxidative stress leading to the cell structural alterations and DNA damage. In contrast, MT supplementation to the S-deprived plants resulted in a significant diminution in reactive oxygen species (ROS) accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…As previously reported for other tomato cultivars [58][59][60][61][62][63], we found that the growth of Solanum lycopersicum cv. Moneymaker seedlings was severely impacted by sulfate starvation.…”
Section: Sulfate Starvation Has a Major Impact On Leaf And Root Growtsupporting
confidence: 89%
See 1 more Smart Citation
“…As previously reported for other tomato cultivars [58][59][60][61][62][63], we found that the growth of Solanum lycopersicum cv. Moneymaker seedlings was severely impacted by sulfate starvation.…”
Section: Sulfate Starvation Has a Major Impact On Leaf And Root Growtsupporting
confidence: 89%
“…Tomato produces fleshy fruits important for the human diet as a source of vitamins and carotenes such as beta-carotene and lycopene [57]. Sulfate deficiency severely reduces the growth of tomato plants [58][59][60][61][62], diminishing biomass, protein concentration, total S in shoots and roots [61,62], chlorophyll contents [59][60][61], as well as yield [63]. Given the economic importance of tomato worldwide, understanding how tomato responds to sulfate starvation at the molecular level and identifying key regulatory components is of paramount importance for sustainable tomato production in the present and future agricultural scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the role of M in plants under abiotic stress, as it acts as an antioxidant and upregulates the expression of antioxidant coding genes/enzymes, thereby reduced formation of ROS [30]. M reacts with ROS, resulting in the formation of M-derivatives that makes M even more capable in the detoxification of ROS, even at low levels [64,65,66] because M can easily cross cellular boundaries and protect the biological system by regulating the metabolic flow of thiol-compounds, such as reduced GSH (Figure 8A) [67]. Furthermore, the obtained results of the present study show that the application of M improved contents of Pro and TSC, and the activity of antioxidant enzymes and non-antioxidant (Figure 7A,C, Figure 9A,B and Figure 10A–D); these factors together resulted in reduced oxidative damage by scavenging ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2), which was consistent with the maintenance of photosynthetic capacity following S supplementation under drought stress as reported by Ma et al 77 in wheat. Adequate S supply helps to counteract the drastic effects of ROS on nucleic acids and proteins through upregulation of antioxidant enzymes such as CAT, GPX and SOD 78 . These antioxidative enzymes serve as scavengers of O 2 and H 2 O 2 and help to prevent the production of toxic HO̅ ̅ ̅ ̅ ̅…”
Section: Discussionmentioning
confidence: 99%